Insomnia and post-traumatic stress disorder: A meta-analysis on interrelated association (n = 57,618) and prevalence (n = 573,665) - Ahmadi, Reihaneh; Rahimi-Jafari, Sama; Olfati, Mahnaz; Javaheripour, Nooshin; Emamian, Farnoosh; Ghadami, Mohammad Rasoul; Khazaie, Habibolah; Knight, David C.; Tahmasian, Masoud; Sepehry, Amir A. (Neuroscience and biobehavioral reviews, 2022)
Posttraumatic stress disorder (PTSD) is a common mental disorder, which is strongly associated with insomnia, yet their epidemiological overlap is poorly understood. To determine the convergent quantitative magnitude of their relationship, PubMed, EMBASE, Scopus, Web of Science, PubPsych, and PsycINFO were searched to identify studies that either reported the correlation or frequency of insomnia symptoms in PTSD and posttraumatic stress symptoms (PTSS), or both. Out of 3714 records, 75 studies met selection criteria and aggregate effect size (ES) estimates were generated for the correlations (K=44, comprising 57,618 subjects) and frequencies (K=33, comprising 573,665 subjects with PTSD/PTSS) of insomnia symptoms in PTSD/PTSS. A medium-size significant correlation was found [ES: 0.52 (CI: 0.47–0.57)] with moderating effects of the COVID-19 pandemic and military service as causes of trauma. The prevalence of insomnia in PTSD/PTSS was 63% [CI: 45%−78%] and was moderated by the cause of trauma as well as the PTSD/PTSS assessment scale. The findings from this meta-analysis highlight the importance of screening and managing insomnia in PTSD patients. •This quantitative meta-analysis identified a medium-size significant correlation (effect size 0.52) between insomnia and PTSD/PTSS.•The meta-analysisdemonstrated that insomnia symptoms are common among individuals with PTSD/PTSS (aggregated frequency 63%).•We hope this work would alert clinicians to consider the importance of screening and treating insomnia in subjects with PTSD.